Nutritional knowledge, sociodemographic, and lifestyle factors as determinants of diet quality – a Polish population-based study - Kucharska, Alicja; Sińska, Beata Irena; Panczyk, Mariusz; Samel-Kowalik, Piotr; Raciborski, Filip; Czerwonogrodzka-Senczyna, Aneta; Boniecka, Iwona; Traczyk, Iwona (Frontiers in Public Health, 2025)
IntroductionNutritional knowledge is a recognized determinant of dietary behaviors, though its impact may vary with sociodemographic and lifestyle factors. To capture such interactions and population variability, advanced methods like moderation and latent class analyses are needed. This study aimed to examine the relationship between nutritional knowledge and diet quality among Polish adults, accounting for socioeconomic determinants, and to identify subgroups at risk of poorer dietary patterns.MethodsA cross-sectional study was conducted using data from two nationally representative surveys (2017–2020), totaling 4,000 adults. Nutritional knowledge was measured with the validated KomPAN questionnaire, and diet quality was assessed with the Diet Quality Index (DQI). Associations were tested via linear regression, moderation analysis explored interactions between knowledge and demographics, and latent class analysis (LCA) identified dietary lifestyle subgroups.ResultsThe mean DQI score was −0.79 (SD = 13.40). Higher nutritional knowledge (β = 0.87, p < 0.001) and higher education were positively associated with diet quality. Women and older adults had better diets; smoking and alcohol consumption were linked to poorer outcomes. Multivariate models confirmed nutritional knowledge, sex, and age as independent predictors. The beneficial effect of knowledge was weaker in older adults (β = −0.49, p < 0.001). LCA revealed three profiles; the poorest diets occurred among younger men with low knowledge and unhealthy behaviors, and younger adults with higher socioeconomic status.ConclusionNutritional knowledge supports better diet quality but may not suffice especially in older adults. Tailored public health strategies are needed for vulnerable groups, including younger men with low knowledge and those with higher socioeconomic status but poor diets.